The Effect of IFRS Application, Stock Price Volatility, and Fundamental Variables on Jakarta Islamic Index - Dellia Nurleli; Masodah Wibisono (Program Studi Manajemen Fakultas Ekonomi Universitas Samudra, 2021)
The movement of the Islamic capital market in recent years is still far from its true potential. Therefore, various researches on Islamic economics are needed to further encourage existing developments. The purpose of this study was to examine the effect of IFRS implementation, Stock Price Volatility, Book to Market, Dividend Yield, and Ownership Structure on Stock Returns. The population of this study is companies registered in the Jakarta Islamic Index (JII) in 2015 - 2018. The sampling method used was purposive sampling and obtained a sample of 14 companies. The data used are the company's annual financial statements that have been audited and published on the Indonesia Stock Exchange website and related company websites, as well as stock trading data obtained through the Yahoo Finance website. The data is processed and analyzed by using multiple linear regression statistical test models and SPSS Version 23 as a tool. The results of this study indicate that partially the Volatility of Stock Prices, Book to Market and Dividend Yield has a significant effect on Stock Returns, while the application of IFRS and Ownership Structure does not affect earnings management practices. Meanwhile, jointly applying IFRS, Stock Price Volatility, Book to Market, Dividend Yield, and Ownership Structure has a significant effect on Stock Returns. This journal discusses the relationship of financial factors to Islamic stocks, where these factors include IFRS, Volatility, and other fundamental variables.